Evaluation of Health Promotion Programs for Changes in Clean and Healthy Living Behavior (PHBS) - Dewi Agustina; Fadillahdwiputri; Dhea Darsanti Eka Putri; Ibnaty Salsabila Salsabila; Sri Wahyuni Siregar; Sastra Putri Wisati Gulo; Tika Zahra Claudya; Airin Raudhatul Jannah; Nayla Azzahra; Maysyarah Tanjung; Sayla Ramadani; Selviani; Anindya Sabrina (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Introduction: Clean and Healthy Living Behavior (PHBS) is an important indicator in improving the degree of public health. However, the implementation of PHBS at the household and school levels still faces various obstacles, such as low knowledge and lack of public awareness. Health promotion programs are designed to encourage behavior change through education and empowerment. This study aims to evaluate the effectiveness of health promotion programs on changes in PHBS behavior in the community. Methods: This study used a quantitative design with a quasi-experimental approach through a pretest-posttest without control group design. The research population is the community in the work area of the health center, with a sample of 60 respondents selected using the purposive sampling technique. The independent variable is the health promotion program, while the dependent variable is the change in PHBS behavior. Data were collected using structured questionnaires and observation sheets, then analyzed using a paired t-test with a significance level of 0.05. Results: The results showed an increase in the average score of PHBS behavior after the health promotion intervention. Statistical analysis showed a significant difference between pretest and posttest scores (p < 0.05), which showed that health promotion programs had an effect on changes in respondents' behavior. Conclusion: Health promotion programs have proven to be effective in improving clean and healthy living behaviors of the community. Continuous program implementation and periodic evaluation are needed to maintain and increase positive behavior changes.